INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND WORK ENVIRONMENT TO EMPLOYEE PERFORMANCE THROUGH WORK SATISFACTION AS AN INTERVENING VARIABLE - Kustiawan, Unggul; Muhammad, Faqih; Aswandi, Edy; Sinaga, Obsatar (International Journal of Psychosocial Rehabilitation, 2020)
Employee performance is important in achieving organizational goals. The presence of transformational leadership styles and a supportive environment will increase employee job satisfaction and will improve employee performance. Therefore, this study aims to involve the majority of transformational leadership and work environment on employee performance through variable job satisfaction. The number of respondents in the study were 200 permanent employees. Analysis of the data used is Structural Equation Modeling (SEM) with the Confirmatory Factor Analysis (CFA) method. The results show that companies must focus on increasing employee job satisfaction and transformational leadership to improve employee performance. Although previous research says that the work environment directly on employee performance. However, this study shows how the work environment has a significant effect on employee job satisfaction. Furthermore, this study unexpectedly found no direct effect between work environment on employee performance. Therefore, this unexpected finding opens new avenues for future research, thus representing an important contribution from this research.